Carter's big break : a novel - Crawford, Brent. (Hyperion, 2010)
Fourteen-year-old Will Carter's summer gets off to a bad start when his girlfriend leaves him, but then he is cast opposite a major star, Hilary Idaho, in a small movie being filmed in his town and things start looking up.